2021
DOI: 10.22541/au.162418885.56100410/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure-Response Relationships for Efficacy and Safety of Filgotinib and its metabolite GS-829845 in Subjects with Rheumatoid Arthritis Based on Phase 2 and Phase 3 Studies

Abstract: Aims:Filgotinib is a potent, oral, JAK1-preferential inhibitor for the treatment of rheumatoid arthritis (RA). This report describes exposure-response (ER) analyses of filgotinib for dose confirmation based on three Phase 3 and two Phase 2 studies in moderate to severe RA patients. Methods:The PK exposures used in ER analyses were derived from population pharmacokinetic analysis. The relationship between filgotinib exposures and various efficacy endpoints (ACR20/50/70 and DAS28) was assessed over octile groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Although still in Phase 1 trials, their feasibility for treating tumors is being further demonstrated. In addition, several inhibitors targeting the JAK/STAT pathway are being tested in multi-stage clinical trials in a variety of diseases, such as Momelitinib (Mesa et al, 2022), Peficitinib (Tanaka et al, 2021), itacitinib (Naing et al, 2022), AZD1480 (Plimack et al, 2013), Fedratinib (Harrison et al, 2022b), Gandotinib (Berdeja et al, 2018), Filgotinib (Meng et al, 2022), Upadacitinib (Deodhar et al, 2022), Decernotinib (Genovese et al, 2016), lestatitinib (Brown et al, 2021), Decernotinib Frontiers in Bioengineering and Biotechnology frontiersin.org (Fleischmann et al, 2015), lestaurtinib (Mascarenhas et al, 2019), abrocitinib (Reich et al, 2022), ritlecitinib (Winnette et al, 2022), brepocitinib (Peeva et al, 2022), deucravacitinib (Mease et al, 2022), delgocitinib (Worm et al, 2022). The JAK/STAT pathway is activated in a variety of common solid tumors contributing to an aggressive phenotype (Roxburgh and McMillan, 2016).…”
Section: Jak/stat Inhibitorsmentioning
confidence: 99%
“…Although still in Phase 1 trials, their feasibility for treating tumors is being further demonstrated. In addition, several inhibitors targeting the JAK/STAT pathway are being tested in multi-stage clinical trials in a variety of diseases, such as Momelitinib (Mesa et al, 2022), Peficitinib (Tanaka et al, 2021), itacitinib (Naing et al, 2022), AZD1480 (Plimack et al, 2013), Fedratinib (Harrison et al, 2022b), Gandotinib (Berdeja et al, 2018), Filgotinib (Meng et al, 2022), Upadacitinib (Deodhar et al, 2022), Decernotinib (Genovese et al, 2016), lestatitinib (Brown et al, 2021), Decernotinib Frontiers in Bioengineering and Biotechnology frontiersin.org (Fleischmann et al, 2015), lestaurtinib (Mascarenhas et al, 2019), abrocitinib (Reich et al, 2022), ritlecitinib (Winnette et al, 2022), brepocitinib (Peeva et al, 2022), deucravacitinib (Mease et al, 2022), delgocitinib (Worm et al, 2022). The JAK/STAT pathway is activated in a variety of common solid tumors contributing to an aggressive phenotype (Roxburgh and McMillan, 2016).…”
Section: Jak/stat Inhibitorsmentioning
confidence: 99%